In-silico Leishmania Target Selectivity of Antiparasitic Terpenoids - Ifedayo Victor Ogungbe; William N. Setzer (Molecules, 2013)
Neglected Tropical Diseases (NTDs), like leishmaniasis, are major causes of mortality in resource-limited countries. The mortality associated with these diseases is largely due to fragile healthcare systems, lack of access to medicines, and resistance by the parasites to the few available drugs. Many antiparasitic plant-derived isoprenoids have been reported, and many of them have good in vitro activity against various forms of Leishmania spp. In this work, potential Leishmania biochemical targets of antiparasitic isoprenoids were studied in silico. Antiparasitic monoterpenoids selectively docked to L. infantum nicotinamidase, L. major uridine diphosphate-glucose pyrophosphorylase and methionyl t-RNA synthetase. The two protein targets selectively targeted by germacranolide sesquiterpenoids were L. major methionyl t-RNA synthetase and dihydroorotate dehydrogenase. Diterpenoids generally favored docking to L. mexicana glycerol-3-phosphate dehydrogenase. Limonoids also showed some selectivity for L. mexicana glycerol-3-phosphate dehydrogenase and L. major dihydroorotate dehydrogenase while withanolides docked more selectively with L. major uridine diphosphate-glucose pyrophosphorylase. The selectivity of the different classes of antiparasitic compounds for the protein targets considered in this work can be explored in fragment- and/or structure-based drug design towards the development of leads for new antileishmanial drugs.